Introduction of the Media Industry and Its Optimization to Residents of Komplek Kebersihan RT13 / RW10 Cengkareng West Jakarta - Mohamad Firdaus; Aditya Herliawan; Fatoni; Aldiansyah; Indra Bakti (PT FORMOSA CENDEKIA GLOBAL, 2023)
There are so many news portals available but not many people know the methods of using journalistic techniques. The purpose of this community service is to make it easier for the community to gain the ability to learn about journalism and demonstrate the use of online news to the community, especially residents of Komplek Kebersihan RT13/RW10 Cengkareng, West Jakarta. The result of community service is getting good knowledge about journalism after studying the Nachannel.my.id News Portal which has various features both in reporting information, videos and polls, which also includes features to promote products. In conclusion, with this community service, the community can gain knowledge about basic techniques of news journalism and also get training in using news portal application features on Android smartphones on mobile devices (smartphones) and laptops used by residents, especially residents of the Komplek kebersihan RT13/RW10 Cengkareng West Jakarta.